Recent trends and practices in Malaysian pharmaceutical supply chain - a qualitative case study - Ahmed Zainul, Abideen; Fazeeda, Mohamad (Universiti Malaysia Pahang, 2018)
The pharmaceutical industry in Malaysia is one of the fastest growing industries that help in increasing the overall country’s revenue to a great extent. Medicinal Drugs are supplied to all regions within the country and as well as to other parts of the world. Generic traditional medicines, vitamins and supplements tops the production output but some of the other rare branded medicines are imported from overseas. Handling a very large variety of product families and different type of medicines is a very challenging job nowadays. Sophisticated methodologies and principles are needed to be followed to suffice the requirements of this complex pharma supply chain network both internally and externally. Time consumed at each and every level of the supply chain plays an important role in deciding the on-time delivery of drugs. A qualitative case study was conducted in a top level Malaysian Pharmaceutical firm to learn about the recent practical strategies and methods adopted by them in achieving on-time delivery and tackle product complexity. This study could also help other middle level small scale industries to develop their supply chain and provide better results to their customers in the future. Success of a country’s economy not only depends on the top level multi-national industries but also depends on the effective running of small scale manufacturing industries. Many useful insights from this study were derived and applied to develop a conceptual framework on the requirements for the effective functioning of any given Malaysian Pharmaceutical supply chain.